Exploring the potential of fennel (Foeniculum vulgare Mill.) as a valuable medicinal plant: a comprehensive (review) - S. Bourakba; A. I. Marakhova; Ya. M. Stanishevskiy; I. A. Vasilenko; V. Y. Zhilkina (Разработка и регистрация лекарственных средств, 2024)
Introduction. Foeniculum vulgare Mill., commonly known as fennel or drugstore dill, is very common as one of the world's oldest spice plants, which has significant economic importance and wide application in the pharmaceutical industry. In medical practice, the fruits of this plant are mainly used, which are included in the State Pharmacopoeia of the XIV edition and are a source of essential oil. They are used as an antispasmodic and carminative agent in the form of an infusion. Fennel grass harvested before flowering is used for food, as well as fruits, stems and inflorescences of the plant as a seasoning.Text. The purpose of this study is to summarize scientific papers on the morphological characteristics, phytochemical compounds, therapeutic properties and basic mechanisms of pharmacological activity of F. vulgare. A systematic literature search was conducted using relevant keywords such as "fennel", "Foeniculum vulgare Mill.", "therapeutic" and "pharmacology" in well-known databases, including ScienceDirect, Scopus, EBSCO and Medline. The search covered articles published before April 25, 2023 in available journals. The results of the study showed that fennel has a wide range of pharmacological properties, including antioxidant, anti-cancer, anti-inflammatory, antifungal, antibacterial and estrogenic effects. These effects can be explained by the presence of aromatic compounds, in particular anethole, estragole and fenchone, which are abundantly present in fennel.Conclusion. The diverse pharmacological properties and rich chemical composition of fennel make it a promising raw material for the development of new medicines. Further study of the therapeutic potential of fennel through in vivo and in vitro studies will contribute to the establishment of mechanisms of pharmacological action of biologically active substances (BAS) of fennel.